Obesity and the receipt of influenza and pneumococcal vaccination: a systematic review and meta-analysis. Issue 1 (December 2016) - Harris, John; Moniz, Michelle; Iott, Brad; Power, Robyn; Griggs, Jennifer
Abstract Background Obesity is a risk factor for inadequate receipt of recommended preventive care services. The objective of this study was to assess the relationship between increasing body mass index and receipt of influenza and pneumococcal vaccinations. A systematic review of the PubMed, Embase, and Web of Science databases was conducted from January 1966 to May 2015 for cohort and cross-sectional studies that assessed the relationship between body mass index and the receipt of vaccinations for influenza and pneumococcus. Separate meta-analyses by obesity classification were performed using a random effects model. Results Six cross-sectional and three cohort studies were included. Average vaccine uptake was 50.4 % for influenza vaccination and 34.6 % for pneumococcal vaccination. Compared to normal weight patients, combined odds ratio (95 % confidence interval) for influenza vaccination was 1.11 (95 % CI 0.97–1.25) for obese (≥30 kg/m2 ) patients. When the outcome was reported by obesity class, combined odds ratios of influenza vaccination were 1.13 (95 % CI 1.02–1.24) for Class I (30–34.9 kg/m2 ) obesity, 1.21 (95 % CI 1.05–1.37) for Class II obesity (35–39.9 kg/m2 ), and 1.19 (95 % CI 0.95–1.42) for Class III obesity (≥40 kg/m2 ) patients. Compared to normal weight patients, combined odds ratio of pneumococcal vaccination were 1.20 (95 % CI 1.13–1.27) for obese patients. When the outcome was reported by obesity class, combined odds ratios were 1.08 (95 % CI 1.04–1.13) for Class I obesity patients, 1.13 (95 % CI 1.10–1.16) for Class II obesity patients, and 1.26 (95 % CI 1.15–1.38) for Class III obesity patients for pneumococcal vaccination. Conclusions Combined findings from the current literature suggest that adults with obesity are more likely than non-obese peers to receive vaccination for influenza and pneumococcus. However, suboptimal vaccination coverage was observed across all body sizes, so future interventions should focus on improving vaccination rates for all adults.